2020
DOI: 10.1097/inf.0000000000002503
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Safety and Effectiveness of Infliximab in Pediatric Patients With Acute Kawasaki Disease

Abstract: Background: In 2015, infliximab was approved for the treatment of patients with intravenous immunoglobulin-refractory Kawasaki disease (KD) in Japan. However, limited real-world data exist on the usefulness of infliximab for acute KD patients. We conducted a postmarketing surveillance study in patients with acute KD refractory to conventional therapies to evaluate the safety (including any live vaccine-related infections) and the effectiveness of infliximab. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
1
22
2
Order By: Relevance
“…Tocilizumab, an IL‐6 receptor antagonist, and Anakinra, an IL‐1 receptor antagonist, have been used for the treatment of severe COVID‐19 in adults, although safety and efficacy has been controversial 51–54 . Infliximab, an anti‐human tumor necrosis factor‐α (TNF‐α) monoclonal antibody, is effective against several inflammatory diseases including KD thus maybe an interesting agent in the MIS‐C population 55,56 . Furthermore, remdesivir, which is a nucleoside analogue that inhibits viral RNA polymerases, has been shown to be associated with the clinical improvement in adults with COVID‐19 57–59 .…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab, an IL‐6 receptor antagonist, and Anakinra, an IL‐1 receptor antagonist, have been used for the treatment of severe COVID‐19 in adults, although safety and efficacy has been controversial 51–54 . Infliximab, an anti‐human tumor necrosis factor‐α (TNF‐α) monoclonal antibody, is effective against several inflammatory diseases including KD thus maybe an interesting agent in the MIS‐C population 55,56 . Furthermore, remdesivir, which is a nucleoside analogue that inhibits viral RNA polymerases, has been shown to be associated with the clinical improvement in adults with COVID‐19 57–59 .…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of CAL risk has become an important issue in KD because of recent advances in the therapeutic strategies available, such as prednisolone therapy ( 15) or treatment with a tumor necrosis factor-alpha antagonist (23), advances that enable stratification of the initial treatment for the patients with a high level of predicted risk. Thus, we carried out this collateral analysis to ascertain the diagnostic accuracy of PTX3, NT-proBNP and Presepsin in detecting CAL before the initial IVIG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…21 In an open-label, observational study from Japan of infliximab (5 mg/kg) for IVIG resistance, 291 patients were enrolled. 22 The majority had already received a second IVIG dose or other therapies and the authors concluded that the safety profile was excellent. Three small, random ised clinical trials of second IVIG versus infliximab (5 mg/kg) enrolling between 24 to 43 subjects have been reported from the USA, 7 Korea, 23 and Japan.…”
Section: Discussionmentioning
confidence: 99%